Contemporary sufism: Piety, politics, and popular Culture - Sharify-Funk, Meena; Dickson, William Rory; Xavier, Merin Shobhana (Taylor and Francis, 2017)
What is Sufism? Contemporary views vary tremendously, even among Sufis themselves. Contemporary Sufism: Piety, Politics, and Popular Culture brings to light the religious frameworks that shape the views of Sufism’s friends, adversaries, admirers, and detractors and, in the process, helps readers better understand the diversity of contemporary Sufism, the pressures and cultural openings to which it responds, and the many divergent opinions about contemporary Sufism’s relationship to Islam. The three main themes: piety, politics, and popular culture are explored in relation to the Islamic and Western contexts that shape them, as well as to the historical conditions that frame contemporary debates. This book is split into three parts: • Sufism and anti-Sufism in contemporary contexts; • Contemporary Sufism in the West: Poetic influences and popular manifestations; • Gendering Sufism: Tradition and transformation. This book will fascinate anyone interested in the challenges of contemporary Sufism as well as its relationship to Islam, gender, and the West. It offers an ideal starting point from which undergraduate and postgraduate students, teachers and lecturers can explore Sufism today.
Created from Fastlane, Scopus look-up